SIGNAL CONVERTER FOR CONTROL AND AUTOMATIZATION SYSTEMS WITH DISTRIBUTED PARAMETERS - Alexey Yuryevich Voronin (Современная наука и инновации)
Some concepts of the class of spatially invariant systems with distributed parameters are considered in this article. The method of construction of the additional device providing spatial compatibility of the set «Object + Additional device» is given because that is necessary for use of a frequency technique of synthesis of systems with the distributed parameters.